Environmental synergisms and extinctions of tropical species - Laurance, William F (Conservation biology : the journal of the Society for Conservation Biology, 2009)
Environmental synergisms may pose the greatest threat to tropical biodiversity. Using recently updated data sets from the International Union for Conservation of Nature (IUCN) Red List, we evaluated the incidence of perceived threats to all known mammal, bird, and amphibian species in tropical forests. Vulnerable, endangered, and extinct species were collectively far more likely to be imperiled by combinations of threats than expected by chance. Among 45 possible pairwise combinations of 10 different threats, 69%, 93%, and 71% were significantly more frequent than expected for threatened mammals, birds, and amphibians, respectively, even with a stringent Bonferroni-corrected probability value (p= 0.003). Based on this analysis, we identified five key environmental synergisms in the tropics and speculate on the existence of others. The most important involve interactions between habitat loss or alteration (from agriculture, urban sprawl, infrastructure, or logging) and other anthropogenic disturbances such as hunting, fire, exotic-species invasions, or pollution. Climatic change and emerging pathogens also can interact with other threats. We assert that environmental synergisms are more likely the norm than the exception for threatened species and ecosystems, can vary markedly in nature among geographic regions and taxa, and may be exceedingly difficult to predict in terms of their ultimate impacts. The perils posed by environmental synergisms highlight the need for a precautionary approach to tropical biodiversity conservation